2016
DOI: 10.2147/jmdh.s120300
|View full text |Cite
|
Sign up to set email alerts
|

Using drawings to explore patients’ perceptions of their illness: a scoping review

Abstract: BackgroundAn emerging approach for investigating patient perspectives of their illness is the use of drawings.ObjectiveThis scoping review consolidates findings from current literature regarding the use of drawings to explore patients’ perceptions and experiences of their illness and treatment.MethodsElectronic databases (Medline, PubMed, Embase, PsychINFO, Cinahl, Art Index and Scopus) and reference lists were searched to identify published English language studies using participant-generated drawings to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 60 publications
(146 reference statements)
0
37
0
1
Order By: Relevance
“… 25 Previous research has also shown children are able to effectively express their thoughts through their drawings with the use of colour, size, and shapes reflecting emotions, worries and even pain. 16 , 25 , 41 , 42 , 60…”
Section: Methodsmentioning
confidence: 99%
“… 25 Previous research has also shown children are able to effectively express their thoughts through their drawings with the use of colour, size, and shapes reflecting emotions, worries and even pain. 16 , 25 , 41 , 42 , 60…”
Section: Methodsmentioning
confidence: 99%
“…Speaking about the strength of this study, we should notice that “seeking participants’ interpretation of their drawings is invaluable as their visual product is highly subjective and can be easily misunderstood from a third perspective” ( Cheung et al, 2016 , p. 641). Three more advantages relate to the feedback from the research participants and triangulation of different data sources, as well as objects and subjects for the data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Students' sketches can be utilized to better understand the perceptions they hold (Cheung, Saini & Smith, 2016). Sketches by pre-service teachers can reveal dispositions, attitudes and experiences.…”
Section: Sketchingmentioning
confidence: 99%